2019
DOI: 10.1111/eea.12760
|View full text |Cite
|
Sign up to set email alerts
|

Predator‐parasitoid‐host interaction: biological control of Rhyzopertha dominica and Sitophilus oryzae by a combination of Xylocoris flavipes and Theocolax elegans in stored cereals

Abstract: Post‐harvest management constraints are economically significant in Africa for a broad range of commodities, resulting in a substantial negative impact on food security and livelihoods. Rhyzopertha dominica (Fabricius) (Coleoptera: Bostrichidae) coexists with Sitophilus oryzae (L.) (Coleoptera: Dryophthoridae) – they infest stored cereal grains, especially in sub‐Saharan Africa, and cause significant losses in storage. Laboratory studies were carried out to determine the efficacy of Xylocoris flavipes (Reuter)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 51 publications
(61 reference statements)
0
3
0
Order By: Relevance
“…The ectoparasitoid wasp Theocolax elegans (Westwood) is a cosmopolitan and generalist pteromalid parasitoid of many major storage insect pests 11 . Augmentative releases of T. elegans can effectively diminish more than 90% of the Rhyzopertha dominica population in stored wheat as well as insect fragments in wheat flour 12 , 13 .…”
Section: Background and Summarymentioning
confidence: 99%
“…The ectoparasitoid wasp Theocolax elegans (Westwood) is a cosmopolitan and generalist pteromalid parasitoid of many major storage insect pests 11 . Augmentative releases of T. elegans can effectively diminish more than 90% of the Rhyzopertha dominica population in stored wheat as well as insect fragments in wheat flour 12 , 13 .…”
Section: Background and Summarymentioning
confidence: 99%
“…Previous research has identified saliva components from S. zeamais that induced the production of synomones in rice and wheat grains, which triggered an indirect defensive response by attracting females of the ectoparasitoid Theocolax elegans (Tang, 2016). This parasitoid has been suggested as a potential biocontrol agent for diverse Coleoptera that develops inside cereal grains or legume seeds, including S. zeamais (Dlamini and Amornsak, 2014;Adarkwah et al, 2019). Endosperm PODs and phenolic compounds have also been established as biochemical resistance factors (Arnason et al, 1992;Sen et al, 1994;García-Lara et al, 2007;López-Castillo et al, 2018b) that reinforce cell walls and improve pericarp thickness and toughness (Saulnier and Thibault, 1999;García-Lara et al, 2004).…”
Section: Implications Of Endosperm Pods In Insect Resistancementioning
confidence: 99%
“…Such insects already consume and damage up to 20% of the yielded grains, and the percentage is supposed to increase due to the rising temperatures [20,21]. Their management has been lately attempted using eco-friendly substances such as inert dusts [22][23][24] and essential oils [25][26][27][28] and employing predators and parasitoids [29,30]. Despite this, phosphine and synthetic insecticides are still widely applied [31,32], and these chemical solutions cause resistance development even in field populations, with severe drawbacks for the environment and non-target species [33,34].…”
Section: Introductionmentioning
confidence: 99%